Analysis of Different Volume of Production of Shrimps, Milk Fishes and Seaweeds in The Province of West NusaTenggara And East Nusa Tenggara - Nuri Muahiddah; Anna Apriana Hidayanti (Jurnal Biologi Tropis, 2022)
The production of shrimp, milkfish and seaweed farming is able to contribute to food sources in Indonesia, especially in the province West Nusa Tenggara (NTB) and East Nusa Tenggara (NTT) areas. This study aims to determine the differences in the volume of production of shrimp, milkfish and seaweed in NTB and NTT in the last decade.This study use t test.  The results of this study were accepts H1 that is there is a significant difference between the volume of shrimp production in NTB and NTT, for the results of the test the different volumes of seaweed production The result obtained is a significance value of 0.004 which is smaller so that it accepts H1 i.e. there is a significant difference between the production volume in the provinces of NTB and NTT, and the last one for the results of the different test results in the volume of milkfish production, the significance value of 0.06 is greater than 0.05, which means that it accepts Ho, there is no significant difference between the volume of milkfish production in the provinces of NTB and NTT. In this study, there was a significant difference in the volume of production of shrimp and seaweed between the provinces of NTB and NTT, so that areas with lower provincial average volumes were able to participate in the management of shrimp and seaweed cultivation in the aquaculture development process from the perspective of natural resources and human resources.